Review of information hiding on Chinese text - Guohua WU; Lichun GONG; Lifeng YUAN; Ye YAO (Tongxin xuebao)
Text information hiding is an important technology to protect the security and integrity of text content.The research progress of Chinese text information hiding was reviewed.According to the clue of Chinese text information hiding,the existing algorithms were divided into three categories,algorithms based on text images,algorithms based on text format and algorithms based on text content.The implementation process of each type of algorithm was elaborated and the advantages and disadvantages of the algorithm were analyzed.At the same time,their principles,embedded capacity and anti-attack capability was compared and analyzed.In addition,the problems existing in Chinese text information hiding technology was summarized,and the research trends were discussed in the future.It is expected to provide reference for research in this field.